1990
DOI: 10.1073/pnas.87.10.3743
|View full text |Cite
|
Sign up to set email alerts
|

An interferon gamma-regulated protein that binds the interferon-inducible enhancer element of major histocompatibility complex class I genes.

Abstract: Interferons (IFNs) induce transcription of major histocompatibility complex (MHC) class I genes through the conserved IFN consensus sequence (ICS) that contains an IFN response motif shared by many IFN-regulated genes. By screening mouse AZAP expression libraries with the ICS as a probe, we isolated a cDNA clone encoding a protein that binds the ICS, designated ICSBP. Protein blot analysis with labeled oligonucleotide probes showed that ICSBP binds not only the MHC class I ICS but also IFN response motifs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
236
1
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(246 citation statements)
references
References 39 publications
7
236
1
2
Order By: Relevance
“…In a transient transfection assay using IRF-1 -/-p48 -/-dKO EFs, mutations in the IRF-E present within the IFN promoters markedly reduced induction by NDV (Y.K, unpublished data). This may suggest that other IRF family members, such as ICSBP (Driggers et al 1990), LSIRF (Matsuyama et al 1995) or IRF-3 (Au et al 1995) play a role in the induction of the IFN genes. After the completion of this work, Yoneyama et al (1996) reported a role for p48 in IFN gene induction by transfecting a dominant-negative form of p48 in a cultured mouse cell line; their results are essentially consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…In a transient transfection assay using IRF-1 -/-p48 -/-dKO EFs, mutations in the IRF-E present within the IFN promoters markedly reduced induction by NDV (Y.K, unpublished data). This may suggest that other IRF family members, such as ICSBP (Driggers et al 1990), LSIRF (Matsuyama et al 1995) or IRF-3 (Au et al 1995) play a role in the induction of the IFN genes. After the completion of this work, Yoneyama et al (1996) reported a role for p48 in IFN gene induction by transfecting a dominant-negative form of p48 in a cultured mouse cell line; their results are essentially consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon (IFN) 2 regulatory factor-8 (IRF-8), previously known as ICSBP (1), is a myeloid cell essential transcription factor that belongs to the IRF family (for review see Refs. 2 and 3).…”
mentioning
confidence: 99%
“…We read with great interest the report by Patnaik et al 1 stating that the monosomal karyotype in myelodysplastic syndromes (MDS), with or without monosomy 7 or 5, is prognostically worse than other complex karyotypes. Monosomal karyotype (MK) has been defined by Breems et al 2 in acute myeloid leukemia (AML) as the presence of at least two autosomal monosomies or of a single monosomy associated to at least one structural abnormality.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Studies of MK in AML have been conducted in patients receiving intensive chemotherapy. 2,3 The MDS study of Patnaik et al 1 included patients analyzed between 1990 and 2010, and thus probably only a fraction of those patients had received hypomethylating agents. We thought useful to review the prognostic value of MK in higher risk MDS treated with AZA.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation